Factors Affecting Medical Device-Related Pressure Injuries in Intensive Care Units - Fatma Ali; Sahar Mohammad; Dalia Ameen (Evidence-Based Nursing Research)
Context: Medical device-related pressure injuries (MDRPI) are a common complication that can occur in critically ill patients and require medical devices in the intensive care unit. MDRPI can occur when pressure from a medical device, such as a ventilator, catheter, or feeding tube, is exerted on the patient's skin for prolonged periods, causing tissue damage and leading to pressure injuries. MDRPI can result in pain, discomfort, prolonged hospital stays, and increased healthcare costs. Therefore, preventing and managing MDRPI in ICU patients is crucial to improving patient outcomes.